2017
DOI: 10.1111/iju.13289
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of contrast‐enhanced ultrasonography and magnetic resonance imaging for the assessment of complex renal cysts: A prospective study

Abstract: Objectives: To compare the diagnostic performance of computed tomography, magnetic resonance imaging and contrast enhanced ultrasonography for the assessment of complex renal cysts. Methods: We carried out a prospective single-center study from January 2012 to December 2013. We included patients with Bosniak category 2F or 3 renal cysts found on computed tomography and reviewed by two expert radiologists. Magnetic resonance imaging and contrast-enhanced ultrasonography were then carried out. Patients with a Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 24 publications
2
30
2
1
Order By: Relevance
“…In Tian et al's [18] study, RMs with FD by pathology were examined with consensus of both CECT and CEUS. DA, [20] reported a significant difference between CEUS and CEMR and CECT, namely, 0.98 (95% CI 0.96-1.0) versus 0.81 (95% CI 0.68-0.94) and 0.56 (95% CI 0.41-0.71; Table 2).…”
Section: Qdp Of Cect and Ceusmentioning
confidence: 96%
See 3 more Smart Citations
“…In Tian et al's [18] study, RMs with FD by pathology were examined with consensus of both CECT and CEUS. DA, [20] reported a significant difference between CEUS and CEMR and CECT, namely, 0.98 (95% CI 0.96-1.0) versus 0.81 (95% CI 0.68-0.94) and 0.56 (95% CI 0.41-0.71; Table 2).…”
Section: Qdp Of Cect and Ceusmentioning
confidence: 96%
“…In summary, the present results confirm that the diagnostic performance of CEUS is at least comparable with that of not only CECT but also CEMR. Concerning PS and pooled NPV for all subtypes of RMs as well as concerning ROC area in evaluating complex CRMs in one study [20], CEUS showed significantly better diagnostic performance than CEMR.…”
Section: Findings In the Context Of Existing Evidencementioning
confidence: 97%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) in comparison with CT is significantly more sensitive and insignificantly more specific in distinguishing category IIF from the category III kidney cyst with a documented tendency to falsely upgrade kidney cysts . In this article by Defortescu et al ., the authors showed that CEUS has higher sensitivity and similar specificity compared with MRI, and that the accuracy of CEUS tends to grow with the operator's experience and knowledge of the examination limits . Complex cysts analyzed in this article did not have calcifications, were not localized in the medial aspect of the kidney and no extremely obese patients were examined.…”
mentioning
confidence: 78%